Kontribusi Intrapersonal Skills dan Interpersonal Skills Terhadap Kesiapan Kerja Pada Mahasiswa Perguruan Tinggi “X” - Entot Suhartono; Zaky machmuddah (JUPIIS: JURNAL PENDIDIKAN ILMU-ILMU SOSIAL, 2020)
Empirically proving the relationship between intrapersonal skills and interpersonal skills to work readiness in "X" college students is the aim of this study. The method used in this research is survey. The population in this study were all "X" college students. The sample used in this study was "X" college final semester students. Purposive sampling with accidental sampling is a sampling technique used in this study. Multiple linear regression in the SPSS 15.0 version program is used as a data processing tool. Obtained 185 respondents in this research. Simultaneous test results show that intrapersonal skills and interpersonal skills significantly affect work readiness for "X" college students. Partially intrapersonal skills and interpersonal skills, both of them significantly affect the work readiness of "X" college students. The implication of this research is the importance of education related to soft skills because this greatly contributes to students preparing themselves when joining the workforce.